Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region - Achilleos, Katerina; Gordon, Dennis P.; Smith, Abigail M. (Zootaxa, 2020)
Collections from relatively deep waters around the New Zealand Exclusive Economic Zone have revealed new species in the cheilostome bryozoan genus Cellaria sensu lato. We describe here seven new species: C. calculosa n. sp., C. curiosa n. sp., C. gracillima n. sp., C. major n. sp., C. spatulifera n. sp., C. stenorhyncha n. sp. and C. macricula n. sp. previously misidentified as C. humilis Moyano, 1983. Four additional species (here called spp. 1, 2, 3, 4) are left in open nomenclature since not enough key taxonomic characteristics were observed to define them as new. Furthermore, some of the newly described species have combinations of taxonomic characters that overlap with those said to characterise Paracellaria and Euginoma. The New Zealand region holds the highest species diversity of Cellaria sensu lato in the world.